Problems of Regulatory Arrangements and The Urgency of Governance Reconstruction in The National Social Security System - Yuli Farianti; Ahmad Redi (Journal Customary Law, 2026)
National Social Security System constitutes a form of state responsibility in guaranteeing the fulfillment of the public’s right to social security as mandated by the 1945 Constitution of the Republic of Indonesia. In its implementation, the administration of the National Social Security System (SJSN) is carried out by the Government together with BPJS Kesehatan and BPJS Ketenagakerjaan as the organizing agencies of national social security programs. Nevertheless, the implementation of the SJSN continues to face various legal and institutional challenges, particularly regarding regulatory disharmony among Law Number 40 of 2004 concerning the National Social Security System, Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS), and Law Number 17 of 2023 concerning Health. Such regulatory inconsistency has resulted in unclear distribution of authority between the Government and BPJS, overlapping institutional functions, and weak coordination in the administration of national social security programs. This study employs a doctrinal legal research method using statutory and library research approaches, analyzed through descriptive-analytical and prescriptive methods. The findings indicate that the regulation of authority relations and governance in the administration of the SJSN has not been implemented optimally. This is reflected in the unclear institutional position of BPJS within Indonesia’s constitutional system, the weak supervisory mechanism, and the dominant role of the Government in several strategic policies concerning the administration of national social security programs. Therefore, legal reconstruction is necessary through regulatory harmonization, clarification of the division of authority between the Government and BPJS, as well as the strengthening of supervisory mechanisms and institutional governance in order to establish a national social security system that is effective, transparent, accountable, and capable of providing legal certainty